RANCANG BANGUN ALAT MUSIK PIANO, HARPA, MARCHING BELL DIGITAL BERBASIS ARDUINO MENGGUNAKAN CAHAYA LASER DAN LDR (Studi kasus : SMP NU 07 Brangsong) - Dendy Kurniawan (Elkom : Jurnal Elektronika dan Komputer, 2018)
A musical instrument is a device created to produce sound. The price of musical instruments themselves varies depending on the type of instrument and the quality of the material used to make the instrument. At NU 07 Brangsong Middle School, there were no instruments except tambourines. That is because there is no funds to buy a musical instrument. The school allocates more funds to buildings or school buildings and scholarship assistance for underprivileged children and intelligent children. Thus students at the school cannot practice or hone their skills in music. From these problems can actually be solved by an arduino-based Piano, Harp, Marching Bell Digital instrument using laser light and LDR. Because this tool can be made at a low cost and can function more than one musical instrument. The working system of this tool is that there are several lasers that will emit light directly on the LDR sensor (in pairs). And when a pair of laser beams and LDR number one are blocked by an object or hand it will emit a piano sound with a "DO" motif. Furthermore, when a pair of laser beams and LDR number two are blocked, it will emit piano sound with the "RE" orientation and so on. This tool is also equipped with buttons that function as a selector of the type of sound that will be generated and the desired octave.